Multigrading and child achievement - Gian Paolo Barbetta; Giuseppe Sorrenti; Gilberto Turati (University of Zurich, Department of Economics, 2019)
We study how grouping students of different grades into a single class (multigrading) affects children's cognitive achievement. To do so, we build instruments to identify the causal effect of multigrading by exploiting an Italian law that controls class size and grade composition. We focus on seven- and ten-year-old second and fifth graders, respectively. Results suggest that attendance in multigrade versus single-grade classes increases students' performance on standardized tests by 19 percent of a standard deviation (24 percent, gross of the class size effect) for second graders, while it has zero effect for fifth graders. The positive impact of multigrading only appears for children sharing their class with peers from higher grades and it is relatively stronger for students from disadvantaged backgrounds.
Keywords: I26; I28; R53; 330; multigrade classes; child development; peer effects; rural areas